(untitled) - Cross, E. A. (New York, 1949)
This book to provides basic literary materials which will enlarge the student's realm of interest, knowledge, and understanding. Because reading is a tool and not an end in itself, we have carefully chosen selections which are not only of highest literary merit but which are related to other secondary school subjects and to the art of living in today's world.
Keywords: Literature; Collections